The characteristics of CTCF binding sequences contribute to enhancer blocking activity - Tsang, F; Stolper, R; Hanifi, M; Cornell, L; Francis, H; Davies, B; Higgs, D; Kassouf, M (Oxford University Press, 2024)
While the elements encoding enhancers and promoters have been relatively well studied, the full spectrum of insulator elements which bind the CCCTC binding factor (CTCF), is relatively poorly characterized. This is partly due to the genomic context of CTCF sites greatly influencing their roles and activity. Here we have developed an experimental system to determine the ability of minimal, consistently sized, individual CTCF elements to interpose between enhancers and promoters and thereby reduce gene expression during differentiation. Importantly, each element is tested in the identical location thereby minimising the effect of genomic context. We found no correlation between the ability of CTCF elements to block enhancer–promoter activity with the degree of evolutionary conservation; their resemblance to the consensus core sequences; or the number of CTCF core motifs harboured in the element. Nevertheless, we have shown that the strongest enhancer–promoter blockers include a previously described bound element lying upstream of the CTCF core motif. In addition, we found other uncharacterised DNaseI footprints located close to the core motif that may affect function. We have developed an assay of CTCF sequences which will enable researchers to sub-classify individual CTCF elements in a uniform and unbiased way.